2020
DOI: 10.37934/cfdl.12.12.116
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Hydrogen Fuel Combustion in Neon-oxygen Circulated Compression Ignition Engine

Abstract: The elimination of NOx emissions for hydrogen combustion in the compression ignition (CI) engine is the primary concern, therefore replacing nitrogen with noble gas is one of the solutions to the eliminated the NOx emission. Current research trend focuses on oxygen-argon as the most suitable working. When using argon, external heating for intake is required for low compression ratio (CR) engines. Hence, neon is another potential solution because it has a high specific heat ratio that is as high as other noble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The authors surveyed the alternative application of nanoparticles in increasing the cooling rate within the house environment for human comforts. Furthermore, work on applying developed wood-polypropylene plastic-cement for building roofing system to suit eco-friendly materials [26][27][28]. This study has carried out using PU form in creating the roofing system for thermal comfort.…”
Section: Results Of Ann Prediction Analysis Of Pu-al Roofing Systemmentioning
confidence: 99%
“…The authors surveyed the alternative application of nanoparticles in increasing the cooling rate within the house environment for human comforts. Furthermore, work on applying developed wood-polypropylene plastic-cement for building roofing system to suit eco-friendly materials [26][27][28]. This study has carried out using PU form in creating the roofing system for thermal comfort.…”
Section: Results Of Ann Prediction Analysis Of Pu-al Roofing Systemmentioning
confidence: 99%
“…Using CFD modelling, neon-oxygen was investigated for the stabilization of hydrogen ignition under standard ambient ingestion conditions. Results indicated that the mean initial hydrogen temperature in neon-oxygen atmospheres was lower than in oxygen-argon environments [35].…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, these countries are in a position to use their resources for their development. Considering these factors, biofuels are considered as one of the main elements which can replace fossils fuels (Mat Taib et al 2020;Reddy and Nanthagopal 2021).…”
Section: Introductionmentioning
confidence: 99%